Organizational Health at mid-West Bank Government Schools: Analysis of Teachers’ and Administrators’ Perceptions - Abdeen, Mohammad (Jordan Journal of Educational Sciences, 2013)
The objective of this study was to investigate the perceptions of teachers and school administrators about organizational health at government schools at mid-West Bank, Palestine. The sample of the study consisted of 62 administrators and 610 teachers from 39 selected schools. An Arabic version of the Organizational Health Inventory OHI was used to collect data. Results revealed that respondents perceived organizational health at their schools positively. Morale dimension got the highest mean, while academic emphasis got the lowest mean. No statistically significant differences among respondents’ perceptions were found.